2006
DOI: 10.1016/j.otohns.2006.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Research education and training in otolaryngology: Meeting summary and research opportunities

Abstract: F ew otolaryngologists-head and neck surgeons participate in comprehensive research training programs, resulting in a diminishing number of physician-scientists in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…Previous articles have raised concerns for inadequate time for research and the importance of research training during residency. 1,6,21 Our data raise several interesting points regarding a new era of resident research. Principally, evidence for increased publications in the work hourrestricted era and research productivity by T32 residents suggest that additional time for research is effective at driving scholarly productivity during training.…”
Section: Discussionmentioning
confidence: 77%
“…Previous articles have raised concerns for inadequate time for research and the importance of research training during residency. 1,6,21 Our data raise several interesting points regarding a new era of resident research. Principally, evidence for increased publications in the work hourrestricted era and research productivity by T32 residents suggest that additional time for research is effective at driving scholarly productivity during training.…”
Section: Discussionmentioning
confidence: 77%
“…Although research is considered integral to advancing the field of otolaryngology, the number of clinician-scientists in otolaryngology continues to diminish. 10 In a survey by Harris, residents were interested in research but were concerned about departmental support for research faculty. 11 Both faculty clinician scientists and residents in otolaryngology reported that a mentor or role model was a critical part to success in the clinicianscientist career path.…”
Section: Discussionmentioning
confidence: 99%
“…The field of otolaryngology–head and neck surgery has seen a similar decline in surgeon‐scientists 2 . Early career otolaryngologists and residents cite potential lost income, family and work‐life balance, length of training, and poor departmental support as obstacles to pursuing a surgeon‐scientist career 3 .…”
Section: Introductionmentioning
confidence: 99%
“…1 The field of otolaryngology-head and neck surgery has seen a similar decline in surgeon-scientists. 2 Early career otolaryngologists and residents cite potential lost income, family and work-life balance, length of training, and poor departmental support as obstacles to pursuing a surgeon-scientist career. 3 Additionally, a study by Narahari et al found that NIH funding to surgeon-scientists, including otolaryngologists, has decreased over the last several years, making it even more challenging for surgeons to have successful research careers.…”
Section: Introductionmentioning
confidence: 99%